Australian burden of disease study: health equity through data disaggregation - Joe Thomas; Balasankar Ganesan; Fahad Hanna (Critical Public Health)
This paper underscores the imperative for enhanced data disaggregation within the Australian Burden of Disease Studies (ABDS). While the ABDS offers a detailed assessment of disease burden, it falls short in providing systematic, disaggregated data – key to equitable healthcare and informed policymaking. Given Australia’s rich linguistic, ethnic, and cultural tapestry, aggregated health data often obscures the true extent of health disparities among diverse groups. The absence of detailed health data can precipitate unforeseen inequities with profound societal repercussions, including social unrest, diminished trust in healthcare and governance, economic downturns, educational gaps, mental health crises, political challenges, and stigmatisation. Such disparities undermine confidence in health systems and advisories, potentially fostering scepticism towards official health communications. Health disparities can lead to economic inadequacies, inflated healthcare expenditures, and stunted economic growth. Communities suffering from poor health are economically disadvantaged, and unexpected health inequities can derail educational achievements, particularly for students from underprivileged backgrounds who may face additional obstacles due to health-related absences or resource scarcity. The mental health burden from health disparities can escalate community-wide psychological distress, manifesting in heightened depression, anxiety, and trauma rates. The stigmatisation of certain groups exacerbates societal divisions and impedes unity. Politically, health inequities demand attention, with leaders facing scrutiny over their handling of these issues. Nevertheless, such challenges can catalyse community solidarity and advocacy for systemic change, fostering resilience. Addressing these disparities necessitates a comprehensive strategy encompassing disaggregated data access, equitable healthcare provision, policy reform, and community involvement. The ABDS 2023 report that Australians lost 5.6 million years of potential healthy life, with chronic disease imposing a more significant toll than premature mortality. The primary contributors to this burden were cancers, mental health conditions, and substance abuse disorders. However, this collective data fails to illuminate the disparate disease impacts on culturally, ethnically, and linguistically diverse populations. The ABD Study highlighted that in 2018, Indigenous Australians lost nearly 240,000 years of healthy life due to illness and early death, equating to 289 years per 1,000 individuals. Conditions like diabetes, cardiovascular diseases, renal disorders, strokes, and respiratory issues were more prevalent among individuals with limited English proficiency compared to fluent speakers. Gestational diabetes rates were notably higher in South Asian, Vietnamese, and African migrants compared to the native-born populace. The article emphasises the critical role of disaggregated health data in shaping effective health policies, optimising resource allocation, and promoting equitable health outcomes aligned with the Sustainable Development Goals. It advocates for integrating such data in public health practices to mitigate health disparities and enhance the welfare of all Australians. Ensuring the widespread availability of legally mandated disaggregated health data is vital for identifying, monitoring, and addressing health disparities within Australia’s multicultural society.